Effects of monoacylglycerols and chitosan on the biogenic amine formation in the flesh of rainbow trout (Oncorhynchus mykiss) - Kateřina Matějková; Martin Křížek; Eva Dadáková; František Vácha; Tamara Pelikánová (Czech Journal of Food Sciences, 2020)
Contents of eight biogenic amines (putrescine, cadaverine, spermidine, spermine, histamine, tyramine, tryptamine and phenylethylamine) were determined in vacuum-packed fillets of rainbow trout (Oncorhynchus mykiss). Fish flesh was treated using a solution of chitosan (2%, w/v) or monoacylglycerols (monocaprylin C8, monocaprin C10, 5%, w/v). The control and treated packs were stored at 3.5 °C for up to 25 days. Samples of good quality did not contain more than 30 mg kg-1 of either putrescine or cadaverine. Exceeding this limit was usually followed by a worsening of the sensory properties of samples. Chitosan was found to be the most potent additive, prolonging the storage time of fillets by approximately four times, compared to control samples. Histamine was not found in any sample treated with chitosan. of the monoacylglycerols, C8 was more efficient compared to C10. All additives are easily applicable to the surface of fish flesh.